A photoelectrocatalytic process that disinfects water contaminated with Mycobacterium kansasii and Mycobacterium avium - Brugnera, Michelle Fernanda; Miyata, Marcelo; Zocolo, Guilherme Julião; Fujimura Leite, Clarice Queico; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2013)
Nontuberculous mycobacteria are resistant to conventional water treatment; indeed, they have been recovered from a wide variety of environmental sources. Here, we applied the photoelectrocatalytic technique using a Ti/TiO2-Ag photoanode to inactivate mycobacteria. For a mycobacteria population of 5 × 108 CFU mL-1, we achieved 99.9 and 99.8% inactivation of Mycobacterium kansasii and Mycobacterium avium with rate constant of 6.2 × 10-3 and 4.2 × 10-3 min-1, respectively, after 240 min. We compared the proposed method with the photolytic and photocatalytic methods. Using a mycobacteria population of 7.5 × 104 CFU mL-1, the proposed Ti/TiO2-Ag photoanode elicited total mycobacteria inactivation within 3 min of treatment; the presence of Ag nanoparticles in the electrode provided 1.5 larger degradation rate constant as compared with the Ti/TiO2 anode (1.75 × 10-2 for M. kansassi and 1.98 × 10-2 for M. avium). We monitored the degradation of the metabolites released during cellular lysis by TOC removal, sugar release, chromatography, and mass spectrometry measurements; photoelectrocatalysis and Ti/TiO2-Ag photoanodes furnished the best results. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag nanoparticles; Disinfection; Mycobacteria; Photoelectrocatalysis; TiO2 nanotubes